THU0326 Short and long-term follow-up with adalimumad in refractory uveitis associated to behÇet's disease. multicenter study of 74 patients. (15th June 2017) - Domínguez-Casas, L; Calvo-Río, V; Beltrán, E; S-Bursόn, J; Mesquida, M; Adán, A; Hernandez, M; H-Grafella, M; V-Pascual, E; M-Costa, L; Sellas, A; Cordero-Coma, M; et al.
Abstract : Objectives: To evaluate the efficacy of adalimumab (ADA) in short and long term follow-up in refractory uveitis of Behçet's disease (BD) Methods: Multicenter study. Ocular inflammation was evaluated according to "SUN working Group" (Am J Ophthalmol 2005;140:509–516), and the macular thickening with OCT. A comparison was carried out between baseline, and follow-up visits. Results are expressed as mean±SD or median [IQR]. Continuous variables were compared with Wilcoxon test. Results: We studied 74 patients/132 affected eyes (39M/35W); mean age 38.7±11.3. The ocular pattern was panuveitis (n=45), posterior uveitis (n=14), anterior uveitis (n=14) and intermediate uveitis (n=1). Before ADA, systemic treatment with corticosteroids, iv metilprednisolone (n=23), Cyclosporin A (58), azathioprine (33), metotrexate (31) and other drugs (28) was used. The dose of ADA was 40 mg/2 weeks/ sc in monotherapy (n=22) or combined (n=52). Most patients showed a rapid and progressive improvement (TABLE). The 24 patients (37 affected eyes) with CME showed a significant improvement. ADA was optimized in 23 (31.1%) that were in remission for 15.3±9 months. Interval of administration was increased to 3 (n=6), 4 (13), 5 (1), 6 (1) and 8 weeks. After a mean follow-up of 13.0±9.7 months after optimization, 21 patients were stable and 2 had a severe flare. In 4 patients ADA was stopped after 35.2±9.3 months in remission. The main adverse effects observed were lymphoma (n=1), pneumonia (1), and 2° bacteriemia by E. Coli (1) Conclusions: ADA was effective in short and long-term follow-up in refractory uveitis associated to BD. Optimization or even suspension of ADA is possible. Disclosure of Interest: None declared